Site-specific iron-57 Moessbauer recoilless fractions in true trioctahedral micas. - Royer, Michel. (University of Ottawa (Canada), 1991)
The accurate determination of site populations from $\sp{57}$Fe Mossbauer spectroscopy requires that spectra be corrected for absorber thickness effects and that site-specific Mossbauer recoilless fractions (f-factors) be known. This thesis uses a novel method to perform thickness-effect corrections, then uses the temperature dependence of the thickness-corrected spectral areas of selected peaks to obtain site-specific f-factors at 80 K and 300 K for the iron sites in true trioctahedral micas. A preliminary study of a biotite single crystal showed the site-specific nature of the f-factors. Five samples--three biotites rich in octahedral Fe$\sp{3+}$, a phlogopite rich in tetrahedral Fe$\sp{3+}$, and a synthetic annite--were then studied to quantify the site-specific f-factors. Our final values, taken to be representative of all true trioctahedral micas, are:++$$\vbox{\halign{#\hfil&&\quad#\hfil\cr&octahedral Fe$\sp{2+}$ sites&f$\sp{\lbrack 2+\rbrack}$ (300 K)&= 0.56 $\pm$ 0.06\cr&&f$\sp{\lbrack 2+\rbrack}$ (80 K)&= 0.82 $\pm$ 0.02\cr&octahedral Fe$\sp{3+}$ sites&f$\sp{\lbrack 3+\rbrack}$ (300 K)&= 0.69 $\pm$ 0.07\cr&&f$\sp{\lbrack 3+\rbrack}$ (80 K)&= 0.87 $\pm$ 0.07\cr&tetrahedral Fe$\sp{3+}$ sites&f$\sp{\langle 3+\rangle}$ (300 K)&= 0.75 $\pm$ 0.10\cr&&f$\sp{\langle 3+\rangle }$ (80 K)&= 0.90 $\pm$ 0.03\cr}}$$(TABLE/EQUATION ENDS)These f-factors are used in conjunction with thickness-corrected sub-spectral areas to obtain the first accurate iron site populations for annite:$$\eqalign{\rm\lbrack Fe\sp{2+}\rbrack /Fe&= (90.5 \pm 1.0)\ \%\cr \lbrack\rm Fe\sp{3+}\rbrack /Fe&= (5.3 \pm 1.0)\ \%\cr \langle\rm Fe\sp3+\rangle /Fe&= (4.2 \pm 0.3)\ \%\cr}$$Experimental uncertainties related to each part of the work are considered in detail, and evaluated where possible.
Keywords: Physics, Condensed Matter.